Identification and Characterization of a Cis Antisense RNA of the rpoH Gene of Salmonella enterica Serovar Typhi - Xiong, Changyan; Li, Xuejiao; Liu, Juanli; Zhao, Xin; Xu, Shungao; Huang, Xinxiang (Frontiers in Microbiology, 2018)
Antisense RNAs from complementary strands of protein coding genes regulate the expression of genes involved in many cellular processes. Using deep sequencing analysis of the Salmonella enterica serovar Typhi (S. Typhi) transcriptome, a novel antisense RNA encoded on the strand complementary to the rpoH gene was revealed. In this study, the molecular features of this antisense RNA were assessed using northern blotting and rapid amplification of cDNA ends. The 3,508 nt sequence of RNA was identified as the antisense RNA of the rpoH gene and was named ArpH. ArpH was found to attenuate the invasion of HeLa cells by S. Typhi by regulating the expression of SPI-1 genes. In an rpoH mutant strain, the invasive capacity of S. Typhi was increased, whereas overexpression of ArpH positively regulates rpoH mRNA levels. Results of this study suggest that the cis-encoded antisense RNA ArpH is likely to affect the invasive capacity of S. Typhi by regulating the expression of rpoH.